南大洋東経110度ラインにおける動物プランクトン群集変動 - 高橋, 邦夫; 飯田, 高大; 小達, 恒夫; 谷村, 篤; 川口, 創; 福地, 光男; Takahashi, Kunio T.; Iida, Takahiro; Odate, Tsuneo; Tanimura, Atsushi; Kawaguchi, So; Fukuchi, Mitsuo (2010)
Antarctica and its surrounding waters are expected to be particularly sensitive and vulnerable to climate change. Zooplankton have much shorter lives and faster population turnover than vertebrate predators. They are expected to respond more rapidly to environmental changes. In the Indian Ocean sector of the Antarctic Ocean, the Japanese Antarctic Research Expedition (JARE) has been conducting routine zooplankton observations with a NORPAC standard net (mesh size: 330m, mouth diameter: 0.45m) every austral summer since 1972/73 season. This program is the only current long-term time-series zooplankton study in the Antarctica, which has been carried on for more than 35 years. Taking the opportunity to use the multiyear samples along a south-north transect at ca. 110ºE between 50ºS and 60ºS, the objectives of the present study were to detect the characteristics of zooplankton communities and to assess the temporal variability in zooplankton abundance and species composition and associated events in this study area. 第32回極域生物シンポジウム 11月30日（火） 国語研究所 ２階講堂 conference object